Acompanhamento fenológico de espécies arbóreas em um fragmento de Caatinga no Município de Upanema, RN - Silva, Mayara Varela Neres da (Universidade Federal Rural do Semi-Árido, 2021)
Phenological monitoring allow the recognition and quantification (intensity) of repetitive biological phenomena throughout the year, thus providing information that can contribute to a better understanding of the processes that occur in a forest area. The aim this work was to monitor the phenological behavior of seven tree species in patch of caatinga, located in the municipality of Upanema, RN, Brazil. Data were collected over a period of two years and ten months. Populations with eight to ten individuals per species were chosen, at least 20 m apart from each other. The phenophases analyzed were leaf fall, leaf flushing, flowering and fruiting, in addition to calculating the synchrony index and analyzing the correlation between the phenophases with the precipitation in the region. The results indicated a highly varied behavior of the analyzed phenophases, with emphasis on the high percentage of leaf fall of Embiratanha and the fruiting of Jurema de embira, which presented fruits during almost the entire follow-up period. Regarding the analysis of synchrony, note that all species had low synchrony between individuals for the flowering and fruiting phenophases. When analyzing the correlation between phenophases and precipitation, it is observed that all species showed a decrease in defoliation at the first signs of rain during the monitoring period and, consequently, sprouting occurred, reaching its maximum and remaining so during the period rainy. It is concluded that the results indicated great variation in phenophases and sudden changes, indicating changes in environmental conditions
Keywords: Fenofase; Nordeste; Espécie Nativa; Sincronia; Phenophase; Northeast; Native Species; Synchrony; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL